CURRENT STATUS OF LARCH PLUS TREES IN THE SUMY REGION - Grygoryeva, V. G.; Samoday, V. P. (Forestry and Forest Melioration, 2017)
Introduction Larch breeding work based on individual selection has been carried out actively in many countries of the world. According to German researchers, a reproductive material from clonal seed orchards of larch hybrids gives an excess of 20–30% by height and 50–80% by wood volume. In addition, the offspring of their plus trees provides 45 % more strait-stemmed trees. Currently, in Ukraine there are 310 larch plus trees in the State Register, 25 of them are grown in the Left-bank Forest-Steppe zone of Sumy region. The aim of the study was to estimate the current status and mensuration characteristics of the plus trees and the oldest larch stands in the Sumy region in which they were selected. Results In 2010, 11 larch trees were selected, including 6 trees (107 years old) in Trostyanetske Forestry Enterprise and 5 trees (114 years old) in Sveske Forestry Enterprise. Now they are included in the State Register of plus trees. In Trostyanetske Forestry Enterprise, plus trees of larch had straight stems and well-developed crowns and were self-pruned well. The trees were in excellent condition. Exceeding the average values of the stand ranged from 3.1 to 11.6% by height and from 6.5 to 49.6 % by diameter. Half of the trees (50 %) belonged to I selection category and the other half did to the II one. According to the investigation results in 2017, taxation indices have changed as follows: the height from 34.0-39.5 m to 33.0-41.0 m, the diameter from 42.3-68.8 cm to 46.0-72.0 cm. In Sveske Forestry Enterprise all 5 trees belonged to I selection category and had the excellent condition. Selected plus trees had straight stems and well-developed crowns and were self-pruned. Their condition was excellent. Exceeding the average values of the stand ranged from 6.4 to 9.1% by height and from 3.4 to 11.1 % by diameter. The observation of 2017 did not reveal the significant changes. The height varied from 38.5 to 39.5 m; the diameter slightly increased: from 54.0-56.0 cm to 56.0-58.0 cm. The observation in 2017 of larch plus trees, selected in 1962–1985 by the age of 94–132 years in the Sumy region, showed that the excess of average indexes of plus trees over the indexes of the stands was 4–67% by height and 33 – 140 % by diameter. Three oldest larch stands in the region, which had been established in 1888-1903, were examined in 2017. At the time of the survey, the stands had high mensuration characteristics: growing stock was 745–910 m3 per ha and yield class was Ia (the highest one). The composition of the stands, as well as larch proportion, has changed considerably since the stands establishment under the influence of biotic and abiotic factors: in all cases, the share of larch increased, regardless of the initial one. Conclusions According to the results of the observation of larch plus trees in 2010 and 2017 in the Sumy region, it has been defined that among 19 trees, selected for the period of 1962–1985, 14 trees remained. They have high mensuration and breeding characteristics and a good health. The excess of average stands’ indices was 4–67 % by height and 33–140 % by diameter. The biggest sizes were found for larch plus trees No 2 (height 50 m, diameter 96 cm) and No 4–6 (heights 40–48m, diameters 69–83 cm). Larch plus trees, selected in 2010 at Sveske and Trostyanetske Forestry Enterprises, correspond to the I and II selection categories and exceed the height of the average stand by 0–11.6 % and the diameter by 0–49.6 %. Old stands at the age of 114–132, where the plus trees of this species were selected, had a good condition and a relatively significant growing stock of larch from 257 to 548 m3 per ha and the total stock of 618–910 m3 per ha in fresh fertile and fresh fairly fertile oak forest conditions. When creating forest plantations with larch, it is advisable to introduce a small part of this species, preventing oak and pine from being replaced by this species with time. With a small percentage of this species, there is a positive effect on the growing stock, the forest stand resistance and the improvement of nutrient status of soil in such plantations. 6 Figs., 3 Tables, 17 Refs.